Tagset reductions in morphosyntactic tagging of Croatian texts - Agić, Željko (Array, 2009)
Morphosyntactic tagging of Croatian texts is performed with stochastic taggers by using a language model built on a manually annotated corpus implementing the Multext East version 3 specifications for Croatian. Tagging accuracy in this framework is basically predefined, i.e. proportionally dependent of two things: the size of the training corpus and the number of different morphosyntactic tags encompassed by that corpus. Being that the 100 kw Croatia Weekly newspaper corpus by definition makes a rather small language model in terms of stochastic tagging of free domain texts, the paper presents an approach dealing with tagset reductions. Several meaningful subsets of the Croatian Multext-East version 3 morphosyntactic tagset specifications are created and applied on Croatian texts with the CroTag stochastic tagger, measuring overall tagging accuracy and F1-measures. Obtained results are discussed in terms of applying different reductions in different natural language processing systems and specific tasks defined by specific user requirements.